Beyond rust : metropolitan Pittsburgh and the fate of industrial America - Dieterich-Ward, Allen (Politics and culture in modern America., 2016)
Beyond Rust is among the first books of its kind to continue past the collapse of American manufacturing in the 1980s by exploring the diverse ways residents of an iconic industrial region sought places for themselves within a new economic order.